2007
DOI: 10.1084/jem.20070819
|View full text |Cite
|
Sign up to set email alerts
|

Impaired nitric oxide bioavailability and l-arginine–reversible endothelial dysfunction in adults with falciparum malaria

Abstract: Severe falciparum malaria (SM) is associated with tissue ischemia related to cytoadherence of parasitized erythrocytes to microvascular endothelium and reduced levels of NO and its precursor, l-arginine. Endothelial function has not been characterized in SM but can be improved by l-arginine in cardiovascular disease. In an observational study in Indonesia, we measured endothelial function using reactive hyperemia–peripheral arterial tonometry (RH-PAT) in 51 adults with SM, 48 patients with moderately severe fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
439
7
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(474 citation statements)
references
References 54 publications
23
439
7
5
Order By: Relevance
“…Accordingly, an apoptosis-coagulation-inflammation imbalance could occur in falciparum malaria, and it is plausible that the vicious cycle of coagulation and inflammation [27][28][29][30][31][32]51 operate and contribute to organ dysfunction, particularly in severe P. falciparum infections. It is important to recognize that nitric oxide (NO) availability may be impaired by hemolysis and hypoargininemia in both human 47 and mice 48 infected with Plasmodium sp. ; it has also been reported that carbon monoxide (CO) suppresses the pathogenesis of experimental cerebral malaria 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, an apoptosis-coagulation-inflammation imbalance could occur in falciparum malaria, and it is plausible that the vicious cycle of coagulation and inflammation [27][28][29][30][31][32]51 operate and contribute to organ dysfunction, particularly in severe P. falciparum infections. It is important to recognize that nitric oxide (NO) availability may be impaired by hemolysis and hypoargininemia in both human 47 and mice 48 infected with Plasmodium sp. ; it has also been reported that carbon monoxide (CO) suppresses the pathogenesis of experimental cerebral malaria 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies on lung function in adult and pediatric patients support the presence of capillary dysfunction manifested as impaired gas exchange and reduced peripheral reactive hyperemic index. 34,35 However, despite evidence of acute lung injury, the presence of overt pulmonary edema in severe malaria varies from 5 to 25% in adults and less than 10% in children. 32 In the latter group, respiratory distress is believed to be mainly central nervous system (CNS)-driven as a response to systemic metabolic acidosis.…”
Section: Clinical Evidence Of Barrier Dysfunction In Severe Malariamentioning
confidence: 99%
“…87 In patients with both P. falciparum and P. vivax malaria, an inverse relationship between the severity of the infection and nitric oxide production/nitric oxide synthase expression has been demonstrated by several studies. 35,88 The decreased NO production and its precursor L-arginine were attributed to a deficiency of arginine and increased arginase activity. These derangements are compounded by the increased cell-free hemoglobin circulating in malaria patients secondary to hemolysis, leading to increased NO scavenging and plasma L-arginine catabolism, and an overall reduction in NO bioavailability as seen in sickle cell disease.…”
Section: Host Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…La arginina es el sustrato para la síntesis de óxido nítrico; los pacientes con malaria presentan bajos niveles de este aminoácido en sangre que se asocian con malaria grave y muerte (70,71). Durante la hemólisis de los glóbulos rojos parasitados se libera arginasa eritrocitaria y hemoglobina, que reducen la disponibilidad del óxido nítrico, la primera, por degradar la arginina y la segunda, por secuestrar el óxido nítrico disponible.…”
Section: Hipótesis De La Biodisponibilidad Del óXido Nítricounclassified